THINK, PAIR AND SHARE: STRATEGI MENGEMBANGKAN KEMAMPUAN PEMAHAMAN BACAAN - Syaiful Islam (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2019)
Classroom Action Research was used in this study. The aim of this study was to boost students’ reading comprehension. There were 40 students participated. The criteria of succes were 1) the score of average class was ≥70 and more than 50% students get score ≥70, the researcher used test to know this result. And 2) Students enjoyed the teaching and learning process. It was found 3 students were qualified as poor, 17 students were fair, 9 students were good, 9 students were very good and 1 student was excellent. The average score was 75.85. The students felt comfortable in the teaching and learning process